Recent trends in the applications of thermally expanded graphite for energy storage and sensors – a review. Issue 22 (12th October 2021) - Murugan, Preethika; Nagarajan, Ramila D.; Shetty, Brahmari H.; Govindasamy, Mani; Sundramoorthy, Ashok K.
Abstract : This review highlight and summarizes the latest developments on the synthesis of TEG based composite materials for their applications in hydrogen storage, thermal energy storage, fuel cells, batteries, supercapacitors, and (bio-) sensors. Abstract : Carbon nanomaterials such as carbon dots (0D), carbon nanotubes (1D), graphene (2D), and graphite (3D) have been exploited as electrode materials for various applications because of their high active surface area, thermal conductivity, high chemical stability and easy availability. In addition, due to the strong affinity between carbon nanomaterials and various catalysts, they can easily form metal carbides (examples: ionic, covalent, interstitial and intermediate transition metal carbides) and also help in the stable dispersion of catalysts on the surface of carbon nanomaterials. Thermally expanded graphite (TEG) is a vermicular-structured carbon material that can be prepared by heating expandable graphite up to 1150 °C using a muffle or tubular furnace. At high temperatures, the thermal expansion of graphite occurred by the intercalation of ions (examples: SO4 2−, NO3 −, Li +, Na +, K +, etc. ) and oxidizing agents (examples: ammonium persulfate, H2 O2, potassium nitrate, potassium dichromate, potassium permanganate, etc. ) which helped in the exfoliation process. Finally, the obtained TEG, an intumescent form of graphite, has been used in the preparation of composite materials with various conducting polymers (examples: epoxy, poly(styrene- co -acrylonitrile), polyaniline, etc. ) and metal chlorides (examples: FeCl3, CuCl2, and ZnCl2 ) for hydrogen storage, thermal energy storage, fuel cells, batteries, supercapacitors, sensors, etc. The main features of TEG include a highly porous structure, very lightweight with an apparent density (0.002–0.02 g cm −3 ), high mechanical properties (10 MPa), thermal conductivity (25–470 W m −1 K −1 ), high electrical conductivity (106–108 S cm −1 ) and low-cost. The porosity and expansion ratio of graphite layers could be customized by controlling the temperature and selection of intercalation ions according to the demand. Recently, TEG based composites prepared with metal oxides, chlorides and polymers have been demonstrated for their use in energy production, energy storage, and electrochemical (bio-) sensors (examples: urea, organic pollutants, Cd 2+, Pb 2+, etc. ). In this review, we have highlighted and summarized the recent developments in TEG-based composites and their potential applications in energy storage, fuel cells and sensors with hand-picked examples.